1985
DOI: 10.1021/bi00346a039
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome rearrangement in vitro. 1. Two phases of salt-induced nucleosome migration in nuclei

Abstract: We have investigated the salt- and temperature-induced rearrangement of nucleosomes in both intact and H1-depleted nuclei from human cells. In agreement with previous reports on the rearrangement of nucleosomes in isolated chromatin or chromatin fragments, we observed a decrease in the average nucleosome repeat length following incubation of nuclei at 37 degrees C in elevated salt concentrations. However, this decrease occurred in two distinct phases. First, incubation of H1-depleted nuclei at 37 degrees C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…These studies demonstrated the existence of two phases of salt-induced nucleosome rearrangement in nuclei in vitro (44). Following the first transition, due to histone octamer sliding, newly repaired DNA remains in an altered (or nonnucleosome) state (43).…”
Section: Discussionmentioning
confidence: 91%
“…These studies demonstrated the existence of two phases of salt-induced nucleosome rearrangement in nuclei in vitro (44). Following the first transition, due to histone octamer sliding, newly repaired DNA remains in an altered (or nonnucleosome) state (43).…”
Section: Discussionmentioning
confidence: 91%
“…However, the presence of bands corresponding to the nucleosome core and a compact dimer suggests that extensive sliding of the cores has taken place; the resulting randomization of nucleosome spacing would result in a smear after micrococcal nuclease digestion. It should be noted that transcriptionally active chromatin regions have been found to be depleted in HI (32) and that removal of HI facilitates sliding of nucleosome cores (33). The cause of the proposed core sliding could be the unwinding and overwinding of DNA due to the passage of the RNA polymerase complexes (34).…”
Section: Discussionmentioning
confidence: 99%
“…When done at 40C, NaCl extraction of H1 should produce little or no nucleosome sliding (9,10). If any sliding occurred during the extraction, it should not affect the results since it occurs before the formation of TDs.…”
Section: Methodsmentioning
confidence: 99%
“…Another interesting feature of Hi-containing nucleosomes is the absence of an obvious peak corresponding to positions +7 and -7 helical turns from the midpoint-i.e., 10 the ends. However, if a small peak were present near the 3' end, it might be obscured by the nearby artifactual peak due to undigested full-length molecules.…”
Section: Plot D)mentioning
confidence: 96%